Abundance, diversity and composition of understory plants along the altitudinal gradient and dominant overstory composition types in the temperate Himalayan region - Sangry, Saveena; Kumar, Praveen; Bhardwaj, D.R.; Dogra, K.S.; Poonam, (Frontiers in Forests and Global Change, 2024)
The Indian Himalayan forests are remarkable landforms experiencing tremendous climatic variation, constituting complex and diversified ecosystems with prominent vegetation zones.Despite their global significance and substantial research efforts focused on plant diversity in the temperate Himalayan region, only a few studies have explicitly assessed the distribution patterns of understory vegetation in relation to forest compositional types along altitudinal gradients. The present study explores the pattern of understory vegetation abundance, species diversity and composition along the altitudinal gradients and among dominant overstory composition types in the Himalayan region. A total of 99 understory species including 37 species in the shrub layer, 62 species in the herb layer vegetation were recorded. The abundance, species diversity and composition of understory vegetation differed significantly along the altitudinal gradient and dominant overstory composition types. The hump shaped pattern along the altitudinal gradient appeared to be the most dominant pattern of plant abundance and species diversity and call for more conservation concern towards the middle elevation zones in the temperate Himalayan region. Moreover, distinct understory vegetation communities were observed at lower elevations compared to higher elevations, with middle elevations exhibiting intermediate vegetation characteristics. The study also highlighted the importance of dominant overstory composition types in shaping the pattern of understory vegetation abundance, species diversity and composition in the temperate Himalayan region. The higher resource conditions associated with broadleaved stands supported higher understory species abundance at lower elevations, while the heterogeneous conditions induced by the mixedwood stands promoted higher understory species diversity. Therefore, management interventions should aim at maintaining diverse range of overstory composition types for conserving biodiversity and their ecological functions in the temperate Himalayan region.